1999
DOI: 10.1103/physrevlett.83.840
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Gap Anisotropy and Quasiparticle Interactions: A Doping Dependent Photoemission Study

Abstract: Comparing ARPES measurements on Bi2212 with penetration depth data, we show that a description of the nodal excitations of the d-wave superconducting state in terms of non-interacting quasiparticles is inadequate, and we estimate the magnitude and doping dependence of the Landau interaction parameter which renormalizes the linear T contribution to the superfluid density. Furthermore, although consistent with d-wave symmetry, the gap with underdoping cannot be fit by the simple coskx-cosky form, which suggests … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
283
3
7

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(339 citation statements)
references
References 30 publications
46
283
3
7
Order By: Relevance
“…3) Er < 2∆max ∼ 70 meV ∼ 9kBTc, which has been deduced either by photoemission measurements in BSCCO [30] or by the position of the B1g mode in Raman scattering; the latter has been measured for all cuprates. This agrees with models which interpret the resonant mode as a magnetic collective mode of the d x 2 −y 2 -wave superconducting state below the electron-hole continuum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3) Er < 2∆max ∼ 70 meV ∼ 9kBTc, which has been deduced either by photoemission measurements in BSCCO [30] or by the position of the B1g mode in Raman scattering; the latter has been measured for all cuprates. This agrees with models which interpret the resonant mode as a magnetic collective mode of the d x 2 −y 2 -wave superconducting state below the electron-hole continuum.…”
Section: Resultsmentioning
confidence: 99%
“…The red full curve shows the doping dependence of the superconducting temperature times 5.3. The figure also shows twice the maximum SC gap as measured in BSCCO by ARPES [30].…”
Section: Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Angle-resolved photoemission spectroscopy (ARPES) experiments indicate that the pseudogap and the superconducting gap have the same momentum dependence across T c , which almost resembles a d x 2 −y 2 -wave, Penetration depth measurements of the superfluid density ρ s (T ) at low temperature probe the low-energy excitations around the nodal points in a d-wave superconductor, and therefore ∆ 0 (π/4). The correspondence between ARPES measurements of ∆ 0 (π/4) and the slope of ρ s (T ) at T = 0 is made however more involved by the presence of the Landau renormalization factors [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is not a crazy idea, because it has been shown that the observed symmetry of the order parameter cannot be fitted with only the lowest harmonics of the d-wave order parameter [18,19,20,21]. Furthermore, a recent experiment with twisted Josephson junctions in the Bi-cuprates [22], is in favor of an extended s-wave order parameter, and has shown the absence of a dwave part in the order parameter.…”
Section: Discussionmentioning
confidence: 99%